2017
DOI: 10.1186/s12909-017-0854-y
|View full text |Cite
|
Sign up to set email alerts
|

Using medical specialty and selection criteria clusters to study specialty selection by Israeli medical students

Abstract: BackgroundDuring their final year of medical school, Israeli students must consider which specialty to choose for residency. Based on the vocational counseling literature we presumed that choices are made by selecting from a cluster of related specialties while considering professional and socio-economic issues.MethodsQuestionnaires distributed to final-year medical students at two Israeli medical schools ascertained inclinations toward various medical specialties and the importance of various selection criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…As aforementioned, the concept by Weiss et al that medical students may chose a cluster of related specialties based on a cluster of socio-economic and occupational features [7] might be particularly useful in understanding the process of specialty choice. Our exploratory factor analysis and the subsequent multilevel logistic regression analyses revealed that career priorities under the 'primary care orientation' category had positive association with choosing general practice, emergency medicine, internal medicine, and paediatrics, all of which could potentially have some primary care aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned, the concept by Weiss et al that medical students may chose a cluster of related specialties based on a cluster of socio-economic and occupational features [7] might be particularly useful in understanding the process of specialty choice. Our exploratory factor analysis and the subsequent multilevel logistic regression analyses revealed that career priorities under the 'primary care orientation' category had positive association with choosing general practice, emergency medicine, internal medicine, and paediatrics, all of which could potentially have some primary care aspects.…”
Section: Discussionmentioning
confidence: 99%
“…sex [3,4] , birthplace [3,4] , and physician parents [5] ) and career priorities [3,6] . Moreover, it has been pointed out that medical students may choose from a group of related specialties based on a cluster of socio-economic and occupational features [7] . Thus, it is necessary to clarify the relationship between demographic and occupational features and examine their effect on career preferences.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge to the FM leadership is twofold. Firstly, to ensure that students expressing interest in FM medicine actually enter FM residencies and are not enticed to switched to other primary care specialties, such as internal medicine and pediatrics, which are in the same interest cluster as family practice [ 13 ]. These two specialties often tempt students to pursue subspecialization leading to their loss as primary care providers.…”
Section: Discussionmentioning
confidence: 99%
“…A 5-point Likert scale was used for answering the questions in Sections 1-4. Results from the current dataset have been published without an in-depth focus on issues surrounding FM [ 10 , 13 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a curriculum map may be generated defining places for different learnings and associated activities [27]. The operationalization of OBL requires active involvement of all stakeholders such as students, faculty, educational environment, curriculum and assessment committees, and advisory board [5]. Backward design model is the most suited approach for designing OBL curriculums [35].…”
Section: Curriculum Designmentioning
confidence: 99%